A new bent-toed gecko of the genus Cyrtodactylus Gray, 1827 (Reptilia, Gekkonidae) from Mount Tompotika, eastern peninsula of Sulawesi, Indonesia - Iskandar, Djoko T.; Rachmansah, Angga; _, Umilaela (Zootaxa, 2011)
Cyrtodactylus batik is a new species described on the basis of seven specimens collected from Mount Tompotika, in the Balantak Mountains, eastern peninsula of Central Sulawesi, Indonesia. This large Cyrtodactylus (up to 115 mm snout– vent length), differs from all other congeners by the combination of striking velvety black dorsal coloration with four irregular dark bands and yellow markings, enlarged tubercles not differently colored from other parts of the dorsum except on the flanks, and the absence of precloacal and femoral pores. The new species, together with C. wallacei and C. jellesmae appear to form an exclusive lineage in Sulawesi.